Development of Public Education in South Kazakhstan in 20-30 years of the XX century: History, Successes and Problems - Tugelova, M.Т. (Karagandy University of the name of acad. E.A. Buketov, 2025)
The relevance of this topic is due to the peculiarities of the current stage of socio-political and cultural development of Kazakhstan, which requires continuous modernization of the structure and content of the educational system. The study of historical experience in solving the problem of growth of the educational level of the population is becoming increasingly important. In this connection, in the article the research of the state policy of the USSR on creation of system of national education, struggle of Bolsheviks with illiteracy of the population of Kazakhstan in 20-30 years of XX century is undertaken. The article analyzes the influence of state-political concepts of the USSR development on the formation of the education system. The author showed that the Soviet state considered the education system as a tool for building a new society, the formation of a skilled working class. At the same time, the development of education is associated with such large-scale tasks as the elimination of illiteracy. An attempt was made to trace the transformations in the education system, to identify quantitative and qualitative indicators that characterize the formation and development of public education in Kazakhstan. The article analyzes the state of school education on the example of development of Russian and Kazakh schools. The article reveals the main characteristics, role and place of general education schools in South Kazakhstan. The analysis of quantitative indicators of education system development in the region for two decades allowed drawing a conclusion about progressive development of school education, about constant growth of the number of students of Kazakh nationality in schools. The role of specialized secondary and higher educational institutions of South Kazakhstan in ensuring the growth of literacy and education of the population of the region is shown.
Keywords: South Kazakhstan; higher educational institution; specialized secondary institutions; school; liquidation of illiteracy; education policy; public education; history of Kazakhstan